2021
DOI: 10.1001/jamaoncol.2021.3523
|View full text |Cite
|
Sign up to set email alerts
|

Ensartinib vs Crizotinib for Patients With Anaplastic Lymphoma Kinase−Positive Non–Small Cell Lung Cancer

Abstract: an oral tyrosine kinase inhibitor of anaplastic lymphoma kinase (ALK), has shown systemic and central nervous system efficacy for patients with ALK-positive non-small cell lung cancer (NSCLC).OBJECTIVE To compare ensartinib with crizotinib among patients with advanced ALK-positive NSCLC who had not received prior treatment with an ALK inhibitor. DESIGN, SETTING, AND PARTICIPANTS This open-label, multicenter, randomized, phase 3 trial conducted in 120 centers in 21 countries enrolled 290 patients between July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 31 publications
4
155
0
1
Order By: Relevance
“…Indeed, the median PFS with first-line treatment using second-generation ALK inhibitors including alectinib exceeds 2 years. 2 , 3 , 4 Whereas four patients (36%) in this study discontinued bevacizumab early due to treatment-related AEs, seven patients (63.6%) overall discontinued bevacizumab early due to either treatment-related AEs, per investigator discretion, or per patient preference, after a median of 9 cycles of bevacizumab (range, 4-48). Long-term addition of an agent that must be administered i.v.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, the median PFS with first-line treatment using second-generation ALK inhibitors including alectinib exceeds 2 years. 2 , 3 , 4 Whereas four patients (36%) in this study discontinued bevacizumab early due to treatment-related AEs, seven patients (63.6%) overall discontinued bevacizumab early due to either treatment-related AEs, per investigator discretion, or per patient preference, after a median of 9 cycles of bevacizumab (range, 4-48). Long-term addition of an agent that must be administered i.v.…”
Section: Discussionmentioning
confidence: 80%
“… 1 Several randomized phase II trials have since demonstrated, however, that more potent and central nervous system (CNS)-active second-generation ALK TKIs (alectinib, brigatinib, and ensartinib) are superior to crizotinib in the first-line setting. 2 , 3 , 4 Alectinib in particular has been commonly used on the basis of the phase III global ALEX trial, which demonstrated significantly prolonged progression-free survival (PFS) compared with crizotinib with a median PFS of 25.7 months versus 10.4 months (by independent review committee assessment). 2 Despite this efficacy, drug resistance develops, and disease progression is inevitable in most patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, also ensartinib, a novel second-generation ALK inhibitor, was demonstrated to be an effective option in the first-line setting, showing significant longer PFS (25.8 months vs 12.7 months, HR, 0.51, p < 0.001) and a higher rate of intracranial response (63.6% vs 21.1%) than crizotinib in phase III eXalt3 study. 42 However, the optimal treatment sequence of ALK inhibitors remains a matter to debate.…”
Section: Discussionmentioning
confidence: 99%
“…However, as is well known, new generation ALK TKI selection and sequencing is still challenging because of the absence of head-to-head comparisons. In fact, second and third generation ALK TKIs, with an approximately 50% reduction in the risk of progression or death compared with crizotinib and with an impressive intracranial activity, overcame a first-line crizotinib approach (Table 3) [4,28,35,40,41,46,48].…”
Section: Systemic Treatment Algorithm: Waiting For a Guidementioning
confidence: 99%
“…In the absence of direct comparative trials, selection requires a comprehensive evaluation of drug systemic activity, CNS efficacy, drug interaction, safety and tolerability. Each ALK inhibitor has, indeed, its own unique side-effect profile with potential specific toxicities: diarrhea, nausea, and emesis with ceritinib; constipation and myalgias with alectinib; early-onset pneumonitis with brigatinib; rash, transaminase elevation, pruritus and nausea with ensartinib, altered lipid levels, cognitive and mood effects with lorlatinib [4,28,35,40,41,46,48].…”
Section: Systemic Treatment Algorithm: Waiting For a Guidementioning
confidence: 99%